THE INFLUENCE OF THE HEAT TRANSFER ON THE NOZZLE MADE FROM DIFFERENT MATERIALS FOR THE E3D VOLCANO SOLUTION (Nonconventional Technologies Review, 2024)
The study aims on the 3D modelling on the E3D Volcano assembly and based on the Fused Deposition Modelling technology a thermal analysis is conducted on the nozzle made from different materials. The main objective is to simulate the loading conditions on the entire assembly focusing on using thermal convection and thermal radiation with different values for the steel, copper, brass convection coefficients as well as for the emissivity coefficients of the steel and aluminium. The thermal simulation will result into 3 levels of simulation each based on different materials used on the E3D Volcano assembly to determine the thermal gradients of each level individually. Although one of the parameters was eliminated, the power parameter [W] and it was replaced with the temperature parameter applied to the resistor with the value of 240 oC to observe the thermal behaviour on the loaded surfaces.
Keywords: heat transfer; influence of materials; E3D Volcano nozzle; additive manufacturing; thermal simulation; data analysis